“We Want Us Alive and Unindebted”. Some Comments on the Economy of Debt and the War against Women in Latin American Neoliberal Capitalism - Saidel, Matías Leandro (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
This article inquires the relationship between the economy of debt as a new dispositive of government and dispossession of populations, and the polymorphic war against women, which most dramatic expression is the proliferation of femicides. Both processes, which characterize Latin American neoliberal capitalism, find their immediate genealogy in state terrorism and anti-subversive wars that proliferated in the region during the 1970s and 80s, in which a new form of low-intensity war on certain parts of the population and the generalized precarization of living conditions emerge. Hence, violence against women and the attempt to recolonize their bodies-territories become more intense, especially following contexts of social struggles against neoliberalization, seeking to impede the autonomous reproduction of life outside capitalist relations.
Keywords: Indebtedness; War against Women; Neoliberal Capitalism; Common; Latin America.